Hyperparasitism by Sphaerellopsis macroconidialis may lower over‐wintering survival of Uromycladium acaciae. Issue 3 (4th May 2021) - Fraser, Stuart; McTaggart, Alistair R.; Roux, Jolanda; Wingfield, Mike J.
Abstract: Uromycladium acaciae has caused an epidemic of wattle rust on Acacia mearnsii in southern Africa since 2013. In April 2016, conidiomata of a species of Sphaerellopsis were observed parasitizing telia of U . acaciae on foliar samples collected from three plantations in Mpumalanga, South Africa. An isolate was identified as Sphaerellopsis macroconidialis based on a phylogenetic species hypothesis of the internal transcribed spacer (ITS) region. This is the first report of this species of mycoparasite from South Africa and on this host. To investigate the seasonal population dynamics of this mycoparasite, the presence of Sphaerellopsis on telia of U . acaciae was assessed monthly between May 2016 and April 2017. The proportion of samples with conidiomata of Sphaerellopsis was greatest between May and November. This period is outside both the peak growing season for A . mearnsii and the main epidemic period for U . acaciae . Results suggest that Sphaerellopsis may have little impact on U . acaciae during epidemic periods of the year but could reduce the over‐wintering survival of this damaging rust fungus and lower initial inoculum loads at the start of the following growth season.